Character-Based Animation Film Media in Students’ Story Writing Learning in SMA - Hasriani Hasriani; Ryan Rayhana Sofyan (PT ARRUS Intelektual Indonesia, 2023)
The problem in this study is how effective the use of character-based animated film media is on students' short story writing abilities so that this study aims to examine the ability to write short stories for class XI SMA Negeri 5 Barru Regency without using character-based animated film media, using character-based animated film media , and found the effectiveness of using character-based animated film media on the ability to write short stories for class XI students of SMA Negeri 5 Barru Regency. This research is an experimental research. The population of this study was all students of class XI SMA Negeri 5 Barru Regency, totaling 343 people. The sample of this research was students of class XI-1 (experimental class) and class XI-3 (control class), each consisting of 30 students. The data collection technique used is the test analysis technique. The entire data obtained was analyzed using descriptive statistical techniques and inferential statistical techniques. The results of the study showed (1) the ability to write short stories of students without using character-based animated film media increased but not too significant, (2) the ability to write short stories of students using character-based animated film media experienced a significant increase, and (3) animated film media Character-based has proven to be effective in learning to write short stories for students, this is in accordance with the results of the t-test conducted.